Benefits of Low-Dose CT Scan of Head for Patients With Intracranial Hemorrhage - Dan Wu; Gang Wang; Bingyang Bian; Zhuohang Liu; Dan Li (SAGE Publishing, 2020)
Objectives: For patients with intracranial hemorrhage (ICH), routine follow-up computed tomography (CT) scans are typically required to monitor the progression of intracranial pathology. Remarkable levels of radiation exposure are accumulated during repeated CT scan. However, the effects and associated risks have still remained elusive. This study presented an effective approach to quantify organ-specific radiation dose of repeated CT scans of head for patients with ICH. We also indicated whether a low-dose CT scan may reduce radiation exposure and keep the image quality highly acceptable for diagnosis. Methods: Herein, 72 patients with a history of ICH were recruited. The patients were divided into 4 groups and underwent CT scan of head with different tube current-time products (250, 200, 150, and 100 mAs). Two experienced radiologists visually rated scores of quality of images according to objective image noise, sharpness, diagnostic acceptability, and artifacts due to physiological noise on the same workstation. Organ-/tissue-specific radiation doses were analyzed using Radimetrics. Results: In conventional CT scan group, signal to noise ratio (SNR) and contrast to noise ratio (CNR) of ICH images were significantly higher than those in normal brain structures. Reducing the tube current-time product may decrease the image quality. However, the predilection sites for ICH could be clearly identified. The SNR and CNR in the predilection sites for ICH were notably higher than other areas. The brain, eye lenses, and salivary glands received the highest radiation dose. Reducing tube current-time product from 250 to 100 mA can significantly reduce the radiation dose. Discussion: We demonstrated that low-dose CT scan of head can still provide reasonable images for diagnosing ICH. The radiation dose can be reduced to ∼45% of the conventional CT scan group.